1997
DOI: 10.2170/jjphysiol.47.241
|View full text |Cite
|
Sign up to set email alerts
|

Functional Uncoupling between the Receptor and G-Protein as the Result of PKC Activation, Observed in Aplysia Neurons.

Abstract: Application of either acetylcholine (ACh), dopamine (DA), histamine (HA), or Phe-Met-Arg-Phe-NH2 (FMRFamide) induces a K+-current response in the identified neurons of Aplysia under voltage clamp. This type of response is mediated by a pertussis toxin (PTX)-sensitive G-protein, Gi or Go. Extracellular application of 60 microM phorbol dibutyrate (PDBu), an activator of protein kinase C (PKC), to these cells markedly depressed all the K+-current responses to ACh, DA, HA, and FMRFamide. The depressing effect of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Earlier we described that members of the MIP family elicit an outward current in D-neurons of Helix pomatia (Kiss et al, 1999). The peptide-elicited outward current could be blocked by Ba 2+ , Cs 2+ , TEA + and 4AP, and in this respect was similar to the K-current evoked by dopamine, histamine, FMRFa and APGWa in Planorbarius, Lymnaea and Aplysia Brezina, 1988;Bolshakov et al, 1993;Sasaki et al, 1997;Tol-Steye et al, 1997). Furthermore, dopamine, histamine, serotonin, acetylcholine, FMRFa and APWGa receptors are all G-protein coupled and all converge onto a single type of K-channel (Ascher & Chesnoy-Marchais, 1982;Brezina, 1988;Bolshakov et al, 1993;Tol-Steye et al, 1997).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Earlier we described that members of the MIP family elicit an outward current in D-neurons of Helix pomatia (Kiss et al, 1999). The peptide-elicited outward current could be blocked by Ba 2+ , Cs 2+ , TEA + and 4AP, and in this respect was similar to the K-current evoked by dopamine, histamine, FMRFa and APGWa in Planorbarius, Lymnaea and Aplysia Brezina, 1988;Bolshakov et al, 1993;Sasaki et al, 1997;Tol-Steye et al, 1997). Furthermore, dopamine, histamine, serotonin, acetylcholine, FMRFa and APWGa receptors are all G-protein coupled and all converge onto a single type of K-channel (Ascher & Chesnoy-Marchais, 1982;Brezina, 1988;Bolshakov et al, 1993;Tol-Steye et al, 1997).…”
Section: Discussionsupporting
confidence: 52%
“…The indirect interaction of G‐proteins with the channels also has been documented in molluscs (Sasaki et al ., 1997). It was reported that the lipoxygenase metabolites of arachidonic acid are involved in the signal transduction route of the K (s) ‐channels (Belardetti et al ., 1989; Buttner et al ., 1989; Bahls et al ., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…An endogenous PTX‐sensitive G i ‐coupled receptor, potentially a D 2 ‐like receptor, was previously described. Upon DA stimulation, it was shown to induce a K + ‐current response in Aplysia sensory neurons (Sasaki et al . 1997).…”
Section: Resultsmentioning
confidence: 99%
“…An endogenous PTX-sensitive G i -coupled receptor, potentially a D 2 -like receptor, was previously described. Upon DA stimulation, it was shown to induce a K + -current response in Aplysia sensory neurons (Sasaki et al 1997). When injected with plasmid coding for the Ap dop1 receptor, sensory neurons still showed an inhibitory response following DA application at concentrations sufficient to induce maximal response of the Ap dop1 receptor (Fig.…”
Section: Expression Of the Ap Dop1 Receptor In Aplysia Sensory Neuronsmentioning
confidence: 92%
“…PDBu has been used previously in Aplysia to activate PKC (Sacktor and Schwartz, 1990;Critz and Byrne, 1992;Wu et al, 1995;Sasaki et al, 1997;Manseau et al, 1998) and has been shown to induce long-term increases in sensory neuron excitability in Aplysia (Manseau et al, 1998). Treatment of cultures with 1.5 hr PDBu (0.25 M) produced no change in glutamate uptake (1 Ϯ 14%; t ϭ 0.08; n ϭ 8; p Ͼ 0.9) measured 24 hr after treatment (Fig.…”
Section: Pkc Is Not Involved In the Long-term Increase In Glutamate Umentioning
confidence: 83%